SOME MORFOLOGIC CHARACTERISTICS OF FOOTBALL PLAYERS - Ljubiša Lilić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
Set of morfologic dimensions as an important factor in selection of football players. The morfologic dimension as an element of set of predicter variables in the level and kvality of motor skills. Tendentions in modelling morfologic structure according to modern systems of football play.